SOCIAL MEDIA AND INSECURE AMONG STUDENTS - Napitupulu, Nurul Hidayah; Marsa, Yummy Jumiati (FORUM PAEDAGOGIK, 2025)
This research aims to explore the impact of social media use on the sense of insecurity experienced by students in Medan City. This study uses a qualitative approach with a phenomenological design, which prioritizes in-depth interviews with 15 informants consisting of 7 main informants, 5 key informants, and 3 supporting informants. Then the data in the field is carried out by data collection techniques with observation, interviews, and documentation. Data analysis techniques with data reduction, data presentation, and conclusion drawn. Data validity techniques with source triangulation, technique triangulation, and time triangulation. The results show that social media has a significant influence on students' mental health, especially in increasing feelings of insecurity related to social comparisons, body image, and often unrealistic standards of success. The majority of informants revealed that social media is a major source of harmful social comparisons, which in turn lowers confidence and increases anxiety. In addition, social media also affects the quality of students' social relationships, with interactions that are more superficial and less based on emotional honesty. This negative impact is further exacerbated by the stigma related to mental health issues, which makes students reluctant to talk about their insecurities. This study also found that support from campuses is needed to reduce the adverse impact of social media use on students' mental health. The resulting recommendations include the importance of providing counseling services, training on healthy social media use, and creating spaces for open discussions about mental health among students. These efforts are expected to help students manage the negative impact of social media and create a campus environment that is more supportive of their mental well-being.